EFEKTIVITAS PENGGUNAAN METODE MEMBACA NYARING BERBANTUAN BUKU RAMAH CERNA DIGITAL KATEGORI B1 TERHADAP KEMAMPUAN MEMBACA PERMULAAN DI KELAS I SDN KEBALEN 02 - Nur Afifah, Aulya; Aryanto, Sani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of early reading skills among first-grade elementary school students due to the use of conventional teaching materials, such as textbooks and blackboards, which fail to capture students’ attention and stimulate their interest in learning. This study aims to determine whether there is a significant effect of using the read-aloud method assisted by digital decodable books B1 category on early reading skills of first-grade elementary school students. This study employs a quantitative approach using an experimental method with a Quasi-Experimental Design, specifically a Non-equivalent Control Group Design. The population in this study consisted of all first-grade students in the 2025/2026 academic year, with a sample of 68 students from two class selected using purposive sampling. The research instrument was the EGRA test. Data were derived from the pretest and posttest results of the experimental and control classes, then analyzed using the Shapiro-Wilk normality test, homogeneity test, and t-test, or the Mann-Whitney U test if the data were not normally distributed. The results of the study indicate that the average initial reading ability of students in the experimental class was 82.00, which was higher than that of the control class at 65.29. Based on the results of the Mann-Whitney test, a significance value of 0.000 < 0.05 was obtained, indicating a significant effect of the use of the read-aloud method assisted by digital decodable books B1 category on early reading ability in Grade 1 at SDN Kebalen 02.